1997
DOI: 10.1111/j.1553-2712.1997.tb03637.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnostic Efficiency of Cardiac Troponin I and Troponin T for Acute Myocardial Infarction

Abstract: Objective: To compare the early diagnostic efficiency of the cardiac troponin I (cTn-I) level with that of the cardiac troponin T (cTn-T) level, as well as the creatine kinase (CK), CK-MB, and myoglobin levels, for acute myocardial infarction (AMI) in patients without an initially diagnostic ECG presenting to the ED within 24 hours of the onset of their symptoms. Methods: A prospective, observational, cohort study was performed involving chest pain patients admitted to a large urban community hospital. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 39 publications
3
49
0
3
Order By: Relevance
“…The studies that have been performed have compared either cTnT or cTnI against CK-MB and myoglobin (38 ). In the studies that have used the newer-generation cardiac troponin assays, the clinical sensitivities of cardiac troponin outperformed those of both myoglobin and CK-MB, findings that are consistent with the fact that increases in cardiac troponin concentration begin 2 to 4 h after the onset of ischemic symptoms (29,(35)(36)(37)(38).…”
Section: Resultssupporting
confidence: 63%
“…The studies that have been performed have compared either cTnT or cTnI against CK-MB and myoglobin (38 ). In the studies that have used the newer-generation cardiac troponin assays, the clinical sensitivities of cardiac troponin outperformed those of both myoglobin and CK-MB, findings that are consistent with the fact that increases in cardiac troponin concentration begin 2 to 4 h after the onset of ischemic symptoms (29,(35)(36)(37)(38).…”
Section: Resultssupporting
confidence: 63%
“…The wide diagnostic window of troponin (10± 15 days) may be due to its profound localization. The cutoå value of 5 mg l ± 1 for CK-MB mass, a method which is more standardized than troponin, agrees with that proposed by the manufacturer and some authors working with other commercial kits [42,43]. We have demonstrated that the sensitivity of CK-MB mass for the diagnosis of AMI during the ® rst 6 h of precordial pain is higher than troponin I using 0.77 and 1.5 mg l ± 1 as the cutoå values.…”
Section: Discussionsupporting
confidence: 72%
“…cTnI contributed significantly to the prognostic power of another scoring system for dogs with severe systemic diseases, the physiologic and laboratory evaluation (APPLE) full score in those patients 38. Using immunoassays with high sensitivity for cTnI improved the sensitivity for detection of myocardial injury as compared to older generation cTnI assays 7, 39, 40, 41…”
mentioning
confidence: 99%